PEMBATASAN HAK BEREKPRESI DAN BERPENDAPAT ASN DALAM BERSOSIAL MEDIA DALAM BERSOSIAL MEDIA DALAM KONTEKS PENCEGAHAN PELANGGARAN NETRALITAS ASN - Batubara, Devara Febrydo (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2024)
The phenomenon of neutrality of the State Civil Apparatus (ASN) seems to be a discussion that always exists in every general election (Pemilu) or regional head election (Pilkada). The State Civil Apparatus Commission (KASN) stated that around 1,678 cases of violations occurred within the bureaucracy and ASN ministries/institutions/regions, which involved violations of ASN neutrality in the period 2020-2022. Based on KASN data, there are violations of neutrality with the motive of utilizing bureaucratic resources, both in the form of support for programs, facilities and infrastructure as well as activities that favor certain candidates. The prohibition on civil servants being sarcastic or uploading and spreading messages attacking or criticizing the government on social media was issued in May in 2018. Ahead of the 2024 elections, which are the main means of realizing democracy in a country. In an effort to maintain the neutrality of ASN from the influence of political parties and to ensure the integrity, cohesiveness and unity of ASN, as well as being able to focus all attention, thoughts and energy on the tasks assigned, ASN are prohibited from becoming members and/or administrators of political parties, as well as running for office with conditions which has been determined by law (UU). Violations of ASN's neutrality, especially during and after the elections that took place in 2009, 2014 and 2019 and ahead of the 2024 elections. Violations can occur in the form of support provided via social media, involvement in campaigns, running for office without being followed by resignation. within the appropriate time frame and so on. This then violates the principle of neutrality and shows the partiality of an ASN which is actually very contrary to the law. Looking at the existing facts, the regulations regarding freedom of opinion held by the State Civil Service (ASN) are very different from the freedom of opinion enjoyed by the Indonesian people. This regulation can certainly limit the space for freedom of expression for State Civil Servants (ASN). However, on the other hand, as a state official, of course all aspects of ASN life are required to comply with the code of ethics that has been regulated by the state. So they face a dilemma when expressing their opinions in public spaces regarding social media in the context of preventing violations of ASN neutrality. Public pros and cons regarding government policies are still occurring, one of which concerns the issue of freedom of opinion and expression on social media, which to this day is still a matter of debate. In addition, the existence of the Information and Electronic Transactions Law (UU ITE) Number 11 of 2008 is still under discussion to this day.